Effects of Withdrawal Speed on the Synthesis of GaN Thin Films by Dip Coating Method - Hamid, Maizatul Akmam Ab; Sha, Shiong Ng (2016)
ln this research, hexagonal wurtzite structure gallium nitride (GaN) thin films were grown on aluminium nitride on silicon substrate [AIN/Si( I I I)] substrate by using sol-gel dip coating deposition method. The effects of the withdrawal speed on the strucutural and surface morphology of the synthesis GaN thin films were investigated. The withdrawal speeds were varied from I 0-100 mm/min. High resolution X-ray diffraction results revealed that the deposited GaN thin films exhibit hexagonal wurtzite structure. The crystallite size increases with increase in withdrawal speed of substrate. Field-emission scanning electron microscopy results show that the grains were uniformly distribute over the film. While the grain size increases with increasing withdrawal speed. The results reveal that the best withdrawal speed is 100 mm/s.